Blackwell's primary care essentials : sports medicine / Thomas Howard; Janus D. Butcher. - Howard, Thomas (Blackwell's primary care essentials series, 2001)
This book covers office orthopedics as well as being a team physician and for sports event coverage. Disorders discussed are organised by orthopedic topics and then by special topics such as sudden death, diabetes and over training.